Practical guidance on the use of laboratory testing in the management of bleeding in patients receiving direct oral anticoagulants - ten Cate H (Vascular Health and Risk Management, 2017)
Hugo ten Cate,1 Yvonne MC Henskens,2 Marcus D Lancé3 1Department of Internal Medicine, Cardiovascular Research Institute, 2Department of Clinical Chemistry, 3Department of Anaesthesiology, Maastricht University Medical Centre, Maastricht, the Netherlands Abstract: Direct oral anticoagulants (DOACs) have demonstrated a favorable benefit–risk profile in several thromboembolic disorders and are increasingly used in routine clinical practice. A number of real-world studies on DOACs are ongoing, and data published so far have shown broadly similar outcomes to those demonstrated in the respective phase III trials. Despite their beneficial attributes, bleeding risk (as with any other anticoagulants) is often a concern for physicians when prescribing DOACs, particularly in elderly patients, those with significant comorbidities, and other high-risk patient populations. Although the absence of routine coagulation monitoring is an advantage of the DOACs, measuring their anticoagulant effect and/or plasma drug levels may be helpful in certain clinical scenarios to help patient management and improve outcomes. In this paper, practical guidance and recommendations are provided for clinical situations in which the test results may aid clinical decision-making, including patients with life-threatening bleeding events, patients without bleeding but with test results indicating a risk of bleeding, for those patients with a suspected thromboembolism while receiving a DOAC, or prior to patients undergoing elective or urgent surgical procedures. Finally, appropriate monitoring of the DOACs could be of substantial benefit to patients, and there is a high potential for development in this area in the future. Keywords: bleeding, direct oral anticoagulants, laboratory testing, perioperative management, practical guidance